2022
DOI: 10.1186/s40001-022-00740-w
|View full text |Cite
|
Sign up to set email alerts
|

EXTL3 could serve as a potential biomarker of prognosis and immunotherapy for prostate cancer and its potential mechanisms

Abstract: Background Exostosin like glycosyltransferase 3 (EXTL3) had been reported to be associated with immune deficiency and play prognostic roles in various cancers. However, little is known about the associations between EXTL3 and prostate cancer (PCa). Hence, this article was designed to clarify their associations. Methods All original data were downloaded from The Cancer Genome Atlas (TCGA) database. Gene set enrichment analysis (GSEA) and CellMiner d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…4C ). Interestingly, the most significantly upregulated genes in Ppm1d T/+ AML ( Zbed3, Runx3, Marcks, Extl3, Pcbp4, Igf2bp3, Plch1 , and Gdf6 ) were previously associated with AML and cancer progression [ 52 58 ]. We compared the expression of these genes in AML patients versus healthy samples using the TNM database [ 42 ], and noted that PLCH1 , ZBED3 , IGF2BP3 , INSM1 , and SLC17A8 were elevated in leukemic patients in comparison to healthy samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4C ). Interestingly, the most significantly upregulated genes in Ppm1d T/+ AML ( Zbed3, Runx3, Marcks, Extl3, Pcbp4, Igf2bp3, Plch1 , and Gdf6 ) were previously associated with AML and cancer progression [ 52 58 ]. We compared the expression of these genes in AML patients versus healthy samples using the TNM database [ 42 ], and noted that PLCH1 , ZBED3 , IGF2BP3 , INSM1 , and SLC17A8 were elevated in leukemic patients in comparison to healthy samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Zhong et al found an up-regulation of COL6A2, which could be a factor in poor prognosis in metastatic ccRCC [31]. Exostosin-like glycosyltransferase 3 (EXTL3), belonging to the EXT family, takes a crucial part in predicting the prognosis of various cancers and immune defciencies [32], but its role in ccRCC remains unknown. HEAT repeat containing 6 (HEATR6) is part of a highly expressed breast cancer amplicon.…”
Section: Discussionmentioning
confidence: 99%
“…EXTL3 can be used as an anticancer gene and is significantly associated with seven signaling pathways in prostate cancer. Therefore, EXTL3 is a potential biomarker for evaluating prognosis and immunotherapy in prostate cancer (Chang et al., 2022). The reported EXTL3 variants were primarily distributed in the EXT domain, affecting the assembly of HS, intercellular communication and biological signal transduction, resulting in defects in the growth and development of the central nervous system and immune system, and abnormal skeletal development.…”
Section: Discussionmentioning
confidence: 99%